Combating Osteoarthritis through Stem Cell Therapies by Rejuvenating Cartilage: A Review - Navneet Kumar Dubey; Viraj Krishna Mishra; Rajni Dubey; Shabbir Syed-Abdul; Joseph R. Wang; Peter D. Wang; Win-Ping Deng (Stem Cells International)
Knee osteoarthritis (OA) is a chronic degenerative disorder which could be distinguished by erosion of articular cartilage, pain, stiffness, and crepitus. Not only aging-associated alterations but also the metabolic factors such as hyperglycemia, dyslipidemia, and obesity affect articular tissues and may initiate or exacerbate the OA. The poor self-healing ability of articular cartilage due to limited regeneration in chondrocytes further adversely affects the osteoarthritic microenvironment. Traditional and current surgical treatment procedures for OA are limited and incapable to reverse the damage of articular cartilage. To overcome these limitations, cell-based therapies are currently being employed to repair and regenerate the structure and function of articular tissues. These therapies not only depend upon source and type of stem cells but also on environmental conditions, growth factors, and chemical and mechanical stimuli. Recently, the pluripotent and various multipotent mesenchymal stem cells have been employed for OA therapy, due to their differentiation potential towards chondrogenic lineage. Additionally, the stem cells have also been supplemented with growth factors to achieve higher healing response in osteoarthritic cartilage. In this review, we summarized the current status of stem cell therapies in OA pathophysiology and also highlighted the potential areas of further research needed in regenerative medicine.